POROUS ANODISATION OF ALUMINUM FILMS WITH PHOTOLITOGRAPHIC MASK UNDER HIGH FORMING VOLTAGES - S. K. Lazarouk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The approach of aluminium porous anodisation has been proposed. Anodisation was realized under high forming voltages with Joule heat sink through aluminium tracks formed by a photolithographic mask. Record high forming voltages have been achieved leads to new tubular oxide structure with wide outer diameter of 50 - 400 nm and the high anodic process anisotropy up to 0,8. The results obtained can be explained by imposing the high electric field in the porous alumina barrier layer.